2016
DOI: 10.1128/aac.00980-16
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antimicrobial Effects of Photocatalysis Using Titanium Dioxide Nanoparticles Are Strongly Potentiated by Addition of Potassium Iodide

Abstract: f Photocatalysis describes the excitation of titanium dioxide nanoparticles (a wide-band gap semiconductor) by UVA light to produce reactive oxygen species (ROS) that can destroy many organic molecules. This photocatalysis process is used for environmental remediation, while antimicrobial photocatalysis can kill many classes of microorganisms and can be used to sterilize water and surfaces and possibly to treat infections. Here we show that addition of the nontoxic inorganic salt potassium iodide to TiO 2 (P25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 42 publications
(36 reference statements)
0
54
0
Order By: Relevance
“…We reported that the addition of KI led to strong potentiation of killing. 17 When the concentration of KI was kept at 10 mM, then hypoiodite was formed as a product, which could eradicate bacteria that were added immediately after light, but not when bacteria were added after a 2 h interval. However, when the KI concentration was increased to 100 mM, then the bactericidal activity in the solution remained after the light was switched off until 24 h later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported that the addition of KI led to strong potentiation of killing. 17 When the concentration of KI was kept at 10 mM, then hypoiodite was formed as a product, which could eradicate bacteria that were added immediately after light, but not when bacteria were added after a 2 h interval. However, when the KI concentration was increased to 100 mM, then the bactericidal activity in the solution remained after the light was switched off until 24 h later.…”
Section: Resultsmentioning
confidence: 99%
“…We generally used concentrations of KI up to 10 mM 15 but recently used concentrations as high as 100 mM in studies with TiO 2 /UVA. 17 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We studied the potentiation of TiO 2 antimicrobial photocatalysis by addition of KI to the suspension of titania nanoparticles and microbial cells [20]. The killing of gram-positive bacteria, gram-negative bacteria, and fungi was increased by up to 6 logs by addition of KI.…”
Section: Effects Of Potassium Iodidementioning
confidence: 99%
“…Huang et al [192] wanted to know whether antimicrobial photocatalysis mediated by TiO 2 could be potentiated by addition of KI and whether the mechanism was via photocatalytic production of iodine/tri-iodide or hypoiodite. Their results showed that addition of the nontoxic inorganic salt KI to TiO 2 (P25) excited by UVA potentiated the killing of Gram-positive bacteria (MRSA), Gram-negative bacteria ( E. coli ), and fungi ( C. albicans ) by up to 6 logs.…”
Section: Methods Of Potentiating Apdimentioning
confidence: 99%